Hydrogen Peroxide (H2O2) Biosensor Based on the Conducting Polymer Using Self-Assembly Technique - Othman, Siti Amira; Radiman, Shahidan (International Journal of Integrated Engineering, 2023)
Biosensors are in principle fabricated by immobilized biomaterials on a detector membrane and combining them with electrochemical equipment. The applications of enzyme-based biosensors can be explored such as in the process of gas detection, medicine, pathogen detection and detection of toxic levels of substances before and after bioremediation. In this study, H2O2 detection was performed using HRP/PANI, HRP/PPY, HRP/PT and HRP/PT/PPY/PANI layers. The HRP/PANI layer from Variable Pressure Scanning Electron Microscopy (VPSEM) image exhibited a dry surface. The HRP/PPY layer exhibited a surface with agglomerate molecules. The HRP/PT layer, on the hand, exhibited a layer surface with almost the same molecular size. This is confirmed by the higher surface roughness value for HRP/PPY compared to other layers obtained via characterization with Atomic Force Microscopy (AFM). The increasing current response for all three layers was arranged in HRP/PANI> HRP/PT> HRP/PPY. VPSEM and AFM images exhibited surfaces with molecules being in an agglomeration state after the H2O2 detection process. In terms of current response, the response rate of H2O2 on the surface of the HRP/PT/PPY/PANI electrode caused the current response obtained to be fast. The roughness value increased with time due to the reaction that took place between the surface of the HRP/PT/PPY/PANI layer with H2O2. The day-based current response showed that day 1 to day 14 exhibited a uniform graph pattern but from day 21 to day 30 there was a change in the graph pattern due to the HRP/PT/PPY/PANI layer undergoing degradation. The activity of the HRP enzyme was studied by looking at its absorption effect for 30 days. From day 1 to day 14, there was a difference in the overall rate of absorption. However, from day 21 to day 30, the rate of absorption remained constant which explains the slowing down of HRP activity